Enzymes enabling the biosynthesis of various C20 polyunsaturated fatty acids in a sea urchin Hemicentrotus pulcherrimus - Yingying Peng; Yutaka Haga; Naoki Kabeya (Open Biology, 2025)
Sea urchins, integral to marine ecosystems and valued as a delicacy in Asia and Europe, contain physiologically important long-chain (>C20) polyunsaturated fatty acids (PUFA) in their gonads, including arachidonic acid (ARA, 20:4n-6), eicosapentaenoic acid (EPA, 20:5n-3) and unusual non-methylene-interrupted fatty acids (NMI-FA) such as 20:2Δ5,11. Although these fatty acids may partially be derived from their diet, such as macroalgae, the present study on Hemicentrotus pulcherrimus has uncovered multiple genes encoding enzymes involved in long-chain PUFA biosynthesis. Specifically, 3 fatty acid desaturases (FadsA, FadsC1 and FadsC2) and 13 elongation of very-long-chain fatty acids proteins (Elovl-like, Elovl1/7-like, Elovl2/5-like, Elovl4-like, Elovl8-like and Elovl6-like A–H) were identified in their genome and transcriptomes. Functional analysis showed that FadsA and FadsC2 function as a Δ5 desaturase and a Δ8 desaturase, respectively, enabling the conversion of 18:2n-6 and 18:3n-3 into ARA and EPA, respectively, along with Elovl, particularly Elovl6-like C. Elovl6-like C demonstrates elongase activity towards both C18 PUFA and monounsaturated fatty acids. Consequently, FadsA and Elovl6-like C enable the synthesis of several NMI-FA, including 20:2Δ5,11 and 20:3Δ5,11,14, from C18 precursors. This indicates that H. pulcherrimus can endogenously synthesize a wide variety of C20 PUFA and NMI-FA, highlighting active biosynthesis pathways within sea urchins.